An analysis of the risk exposure of adopting IPV6 in enterprise networks - Berko, Istvan Sandor (Rhodes University, Faculty of Science, Department of Computer Science, 2015)
The IPv6 increased address pool presents changes in resource impact to the Enterprise that, if not adequately addressed, can change risks that are locally significant in IPv4 to risks that can impact the Enterprise in its entirety. The expected conclusion is that the IPv6 environment will impose significant changes in the Enterprise environment - which may negatively impact organisational security if the IPv6 nuances are not adequately addressed. This thesis reviews the risks related to the operation of enterprise networks with the introduction of IPv6. The global trends are discussed to provide insight and background to the IPv6 research space. Analysing the current state of readiness in enterprise networks, quantifies the value of developing this thesis. The base controls that should be deployed in enterprise networks to prevent the abuse of IPv6 through tunnelling and the protection of the enterprise access layer are discussed. A series of case studies are presented which identify and analyse the impact of certain changes in the IPv6 protocol on the enterprise networks. The case studies also identify mitigation techniques to reduce risk.
Keywords: International Workshop on Deploying the Future Infrastructure; Computer networks; Computer networks -- Security measures; Computer network protocols